A microfluidic device for hydrodynamic trapping and manipulation platform of a single Biological cell - Ahmad Khalili, Amelia (MDPI AG, 2016)
To perform specific analysis for the single cell, individual cells have to be captured and separated from each other before further treatments and analysis can be carried out. This paper presents the design, simulation, fabrication, and testing of a microfluidic device for trapping a single cell/particle based on a hydrodynamic technique. A T-channel trapping chip has been proposed to provide single-cell trapping and consequently could be a platform for cell treatments and manipulations. A finite element T-channel trapping model was developed using Abaqus FEA™ software to observe it's trapping ability by optimizing the channel's geometry and RhMain/RhTrap ratio. A proof of concept demonstration for cell trapping in the T-channel model was presented in the simulation analysis and experimental work using HUVEC cell aggregate. The T-channel was found to be able to trap a single cell via the hydrodynamic trapping concept using an appropriate channel geometry and RhMain/RhTrap ratio. The proposed T-channel single-cell trapping has potential application for single cell characterization and single 3D cell aggregates treatments and analysis.